Determining attributes of urban plaza for social sustainability - Harun, Nor Zalina; Zakariya, Khalilah; Mansor, Mazlina; Zakaria, Khairunnisa (Elsevier, 2014)
Social sustainability can be attributed to various physical factors in the city. Among the important factors that are often associated with social sustainability is the availability of public spaces. However the success of this public space is still disputable. This study is about the urban plaza and its role in the formation of a sustainable and vibrant city. It asserts that the existence and preservation of such spaces in a city is vital.The findings from the study highlights that urban plaza has more than one meaning, strong reason that encourages the locals to utilize the area.